Early Modern Women Poets, edited by Jane Stevenson and Peter Davidson - Jaine, Tom (Petits Propos Culinaires, 2024)
Early Modern Women Poets, edited by Jane Stevenson and Peter Davidson (Oxford University Press, 2001: ISBN 0-19-924257-7 paperback, 0-19-818426-3 hardback: 585 pp., £25 paperback, £65 hardback).